Labour market under-utilisation of recent higher education graduates: New Australian panel evidence - David Carroll; Massimiliano Tani (Institute for the Study of Labor (IZA), 2011)
Recent research into the Australian labour market has reported that a substantial proportion of the tertiary-educated labour force is under-utilised relative to their level of education, echoing findings from an expanding international literature. This paper uses recent panel data from the 2010 Beyond Graduation Survey to analyse the incidence of labour force under-utilisation amongst recent Australian graduates and its effect on their wages, with an under-utilised graduate defined as a one who is in a job for which a sub-degree qualification would suffice. We find that 26% of graduates were under-utilised immediately after course completion and 15% were under-utilised three years later, although this varied considerably between subgroups. Recent graduates were much more likely to remain under-utilised than become under-utilised later in their careers. Being under-utilised appears to affect the earnings of different graduate age groups in different ways. Controlling for unobserved heterogeneity, we find that younger graduates tend to earn the same mean wages regardless of whether or not they are under-utilised, while older under-utilised bachelor degree graduates are at a significant wage disadvantage relative to their peers. This is suggestive of a graduate skills surplus and, by extension, inefficient public and individual investment in human capital.
urn:nbn:de:101:1-201111029337
Keywords: I23; J24; 330; graduate labour market; human capital; panel data; Unterbeschäftigung; Akademiker; Schätzung; Australien